The Effect of Service Quality and Perceived Value on Brand Loyalty Mediated by Customer Satisfaction at Mie Gacoan Yogyakarta - Nur Zakiyah Mukarromah; Yuni Istanto; Wisnalmawati Wisnalmawati (Westscience Press, 2023)
This study aims to determine the effect of service quality and perceived value on brand loyalty mediated by customer satisfaction at Mie Gacoan restaurants in all areas in Yogyakarta. This research is explanatory research with survey method. The population in this study were all consumers of Mie Gacoan in the Yogyakarta branch. Sampling using purposive sampling method. This type of statistical analysis uses PLS 3.0. And the results showed that directly all independent variables have a significant positive effect on brand loyalty. Indirectly service quality, perceived value has a significant positive effect on brand loyalty which is mediated by customer satisfaction.